Polypharmacy in patients with chronic-degenerative diseases in a remote community, Puebla- México. - Sánchez-Hernádez, Veronica; Morales-Pérez, Marlen; Osorio-Espinoza, Angélica (Revista Médica de Risaralda, 2022)
Objective: To determine if patients with chronic degenerative diseases between 50-90 years of age have polypharmacy and drug interactions, at the Huajoyuca Health Center of Palacios, between June 2018-June 2019. Methodology: A descriptive, observational, non-experimental, statistical, retrospective, cross-sectional, unicentric research was carried out. The sample consisted of 56 files according to the inclusion criteria. Data were analyzed according to descriptive statistics and frequency histograms. Results: The mean age is 67.11 ± 9.6 years. There was a higher prevalence of polypharmacy in the 60-69 age range. Due to excessive medication consumption, women make up 82 percent of those affected. Patients with chronic-degenerative disorders are the most likely to have polypharmacy, and those with comorbid conditions even more, it was observed that the consumption and frequency of medications per patient is 4.08 ± 1.56 medications. The top drugs consumed daily are metformin (17.41%), hydrochlorothiazide (12.05%), B vitamin, acetylsalicylic acid glibenclamide with (11.16%), losartan (8.03%), enalapril (6.69%), captopril (4.91 %). 38 patients with (68%) had minor polypharmacy, 17 patients with (30%) had major polypharmacy, and 1 patient with (2%), had excess polypharmacy. Conclusion: In order from highest to lowest, patients with type 2 diabetes mellitus have minor polypharmacy, unlike hypertensive and dyslipidemic patients. The gender most affected by polypharmacy is the female with 82% vs. 18% the male gender of the population studied.